A CRITICAL ANALYSIS IN COMPLIANCE AND GOVERNANCE IN THE INTEGRATION OF PHARMACY, OPTICAL, AND HEALTH SERVICES MANAGEMENT - 1NASSER ALI DUHYMAN ALYAMI, 2MASOUD MOHAMMAED HUSAIN ALMANSOUR, 3FAHAD SALEM SALEH AL AQEEL, 4ABDULLAH FISAL AHMAD AL HAIDER, 5MANA NASSER HADI AL AGEEL, 6NASSER MOHAMMED SALEH AL AQIL, 7MOHAMMAD MOEEDH ALBAHRI, 8MANA MASOUD MANA AL ABBAS, (Chelonian Research Foundation, 2022)
The integration of pharmaceutical, optical, and healthcare administration presents unique challenges and openings for compliance and administration. This essential appraisal investigates key issues encompassing compliance and administration more broadly. This article draws on existing writing, synthesizes methodological and observational discoveries, investigates complex suggestions, presents comes about and discoveries, and examines the effects on partners. The dialog gave patient into the best practices and ranges with potential for change and brought about proposals to progress compliance and administration in trade administration, pharmaceuticals, optical, and healthcare. Keywords: Compliance, Governance, Integration, pharmacy, Optical, Health Services